LITERASI MEMBACA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA BUKU FIKSI DI SMP NEGERI 11 MEDAN - H Sibarani, Romian; Panigoran Siburian; Christin Agustina Purba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Literacy culture plays a crucial role in life because knowledge is essentially discovered through reading and writing activities. By reading more, individuals can learn many things they previously did not know. There are numerous benefits of reading in life, such as broadening horizons and increasing knowledge, improving language skills, enhancing imagination, and many more.The low reading literacy in Indonesia makes Indonesian education lag behind other countries. Based on the results of the 2022 Programme for International Student Assessment (PISA) Survey, Indonesia's reading literacy score has decreased compared to 2018. One of the causes of the low literacy culture in Indonesia is the lack of interest and habit of reading. Interest in reading needs to be formed and trained from an early age, because interest in reading is not something that is automatically possessed from birth. One of the efforts made by the government is to implement the School Literacy Movement (GLS). Based on the results of the study from the pre-action stage to cycle III, there was a significant increase in students' reading literacy skills for fiction books at SMP Negeri 11 Medan. At the pre-action stage, the average student score only reached 66.5 with a completion of 53.13%. After the action was carried out in cycle I, the average score increased to 68.44 with a completion of 34.38%. Improvements continued in cycle II with an average score of 76.13 and completion reaching 84.38%. The peak occurred in cycle III, where the average student score increased to 78.19 and completion reached 93.75%. This increase shows that the implementation of reading literacy activities in a gradual and structured manner can significantly improve students' reading skills for fiction texts.